2007
DOI: 10.1084/jem2044oia9
|View full text |Cite
|
Sign up to set email alerts
|

ASK1-dependent recruitment and activation of macrophages induce hair growth in skin wounds

Abstract: Abbreviations used in this paper: ASK1, apoptosis signal-regulating kinase 1; BMDM, bone marrow-derived macrophage; DC, dendritic cell; ERK, extracellular signal-regulated kinase; IL, interleukin; MCP-1, monocyte chemoattractant protein-1; MEF, mouse embryonic fi broblast; MHC, major histocompatability complex; MIP-1α, macrophage infl ammatory protein-1α; MSP, macrophagestimulating factor; WT, wild-type.The online version of this article contains supplemental material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…Appendages do not readily develop within a scar, but it has been reported that inflammation can promote appendage re-growth (Osaka et al, 2007), and this is thought to require re-enactment of the epidermal developmental program, in which Wnt signalling has a pivotal role (Ito et al, 2007).…”
Section: Resolutionmentioning
confidence: 99%
“…Appendages do not readily develop within a scar, but it has been reported that inflammation can promote appendage re-growth (Osaka et al, 2007), and this is thought to require re-enactment of the epidermal developmental program, in which Wnt signalling has a pivotal role (Ito et al, 2007).…”
Section: Resolutionmentioning
confidence: 99%
“…It is expected that ASK1 functions as a tumor suppressor gene in cancer cells and is a potential therapeutic target for anticancer drugs. Indeed, downregulation of ASK1 activity has been detected in several malignant cancers and associated proliferation of cancer cells (14,15). Conversely, anticancer therapeutics, including radiotherapy and chemotherapy, can induce cancer cell apoptosis by activating ASK1 (16).…”
Section: Introductionmentioning
confidence: 99%
“…Because 14-3-3 proteins bind most members of the MAP3K family, this may represent a general mechanism by which 14-3-3 and ASK2 exist in a heteromeric complex, and are dephosphorylated at S967 and S964, respectively. In this complex, ASK2 facilitates ASK1 activation through phosphorylation of T838, whereas ASK1 exhibits positive feedback regulation on ASK2 through stabilization of the ASK2 protein (Osaka et al, 2007). These activities culminate in the activation of ASK1 downstream signals, leading to ASK1-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ASK1 is also activated by unfolded protein response-induced endoplasmic reticulum stress (Nishitoh et al, 2002). Recently, important physiological and pathological roles of ASK1 have emerged to include the regulation of innate immunity, cellular differentiation, and various human diseases such as cardiac hypertrophy and remodeling, insulin resistance, neurodegeneration and tumorigenesis (Izumiya et al, 2003;Matsuzawa et al, 2005;Imoto et al, 2006;Osaka et al, 2007;Iriyama et al, 2009). Because of its importance as a central mediator of diverse developmental and stress signals, ASK1 activation is tightly controlled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation